1989
DOI: 10.1007/bf02917177
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced alterations in ocular trace elements

Abstract: The present report demonstrates, for the first time, that feeding rats 50 ppm cadmium for just 7 wk results in detectable levels of cadmium in the eye of rats. Furthermore, these ocular cadmium concentrations affect significant alterations in the levels of the essential trace elements selenium, calcium, iron, and copper in the eye. Rats were fed a low-selenium (less than 0.02 ppm selenium), high-copper basal diet (50 ppm copper) supplemented with 0, 0.1, and 0.5 ppm selenium. The animals were either untreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Heavy metals have the capacity to replace previously bound metals and change the ocular metal concentrations [14,15]. Erie et al reported that lead accumulated in the retinal pigment epithelium, choroid, ciliary body, and the retina of humans at concentrations greater than found in the blood [16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Heavy metals have the capacity to replace previously bound metals and change the ocular metal concentrations [14,15]. Erie et al reported that lead accumulated in the retinal pigment epithelium, choroid, ciliary body, and the retina of humans at concentrations greater than found in the blood [16].…”
Section: Discussionmentioning
confidence: 98%
“…IOP measurements were performed seven times (at 6,9,12,15,18,21,24 o'clock as 24-h IOP measurements) in POAG patients. Patients whose highest IOP was below 14 mm Hg were enrolled in the low-IOP group and patients whose highest IOP was above 15 mm Hg were enrolled in the high-IOP group.…”
Section: Methodsmentioning
confidence: 99%
“…An increase of Cd in eyes with age has been found in human retina as result of smoking, increasing risk of macular degeneration [ 46 ]. Jamall & Roque [ 47 ] found that a daily ingestion of 50 ppm Cd results in detectable accumulation after seven weeks in the eye of rats, implying that Cd in the diet can result in Cd accumulation in the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals have the capacity to replace previously bound metals and change the concentrations of other metals in patients’ tissues, including ocular tissues [ 125 ]. Therefore, in several publications appearing in ophthalmic literature, the influence of heavy metals on the incidence and morbidity of glaucoma was examined.…”
Section: Trace Elements In Glaucomamentioning
confidence: 99%